Effects of Drilling Technology on Mini-Implant Primary Stability: A Comparison of the Mechanical Drilling and Femtosecond Laser Ablation - Zhang, Wenbin; Alghannam, Fahad; Zhu, Yingchao; Zhang, Jianfei; Wohl, Gregory R; Haugen, Harold K.; Qin, Zhipeng; Xie, Guoqiang; Fang, Qiyin; Shen, Steve Guofang (Frontiers in Physics, 2021)
Objectives: Primary stability is a fundamental prerequisite in predicting the prognosis of a mini-implant (MI) as a skeletal anchorage. This study aims to evaluate the influence of implant site preparation technology on the primary stability of MI. Methods: A total of 108 bovine cortical bone samples were fabricated to three thicknesses (0.5, 1.0, and 1.5 mm). For each thickness group, the samples were divided into three subgroups: I (without site preparation), II (site preparation with a mechanical drill), and III (site preparation with femtosecond laser ablation). After MI insertion into these samples, the pull out strength of MI was measured by lateral pull out tests. Results: For the 0.5 mm thickness samples, the lateral pull-out strength was 9.9±2.7 N in subgroup I, 6.7±2.1 N in subgroup II, and 15.2±2.6 N in subgroup III. For the 1.0 mm thickness samples, the lateral pull-out strength was 39.3±2.5N in subgroup I, 38.2±2.7N in subgroup II, and 46.3±1.7 N in subgroup III. For the 1.5 mm thickness samples, the lateral pull-out strength was 73.9±4.8 N in subgroup I, 70.1±2.8 N in subgroup II, 75.0±2.2 N in subgroup III. No signs of carbonization or substantial cracking were visible in any of the bone samples. Conclusion: Site preparation with laser ablation significantly improved the lateral pull-out strength over mechanical preparation and control (no site preparation) in thinner cortical bone samples (1.0 and 0.5 mm). Such improvement in lateral pull-out strength decreases as the samples become thicker and diminishes in thick (1.5 mm) cortical bone samples.